Traditional and Econometric Approach to Assessing the Economic Efficiency of Financial Institutions - Jacek BARBURSKI (Communications of International Proceedings, 2021)
The assessment of the economic efficiency of financial institutions is an extremely important aspect of ​​evaluating their activities. The assessment uses various methods and approaches. Yet, despite extensive research conducted in this area to date, it is necessary to search for new methods, complement one method with another, use the so-called integrated methods, as well as making comparisons of the obtained research results. It often occurs that the results and rankings of effectiveness prepared on the basis of different measurement methods are not compatible. This paper is theoretical, and it aims mainly to present traditional and econometric methods of assessing the economic effectiveness of institutions. In particular, these methods relate to the assessment of banks as financial entities of major importance to each country’s economy. In this paper, traditional (or classic) methods are understood as methods of assessing economic efficiency using diverse types of indicators, mainly derived from financial reporting. Considering econometric methods, it focuses on stochastic marginal cost, revenue and profit models. It also compares both the considered methods, in particular, their underlying assumptions, calculation methods and advantages and disadvantages of each of the discussed methods.
Keywords: Measurement of Bank’ Efficiency; Economic Efficiency; Cost Efficiency; Profit Efficiency; Stochastic Frontier Models